Characterization and expression analysis of immune-related genes in the red swamp crayfish, Procambarus clarkii in response to lipopolysaccharide challenge. Issue 95 (December 2019) - Jiao, Ting; Yang, Ting-Ting; Wang, Dong; Gao, Zhen-Qiu; Wang, Jia-Lian; Tang, Bo-Ping; Liu, Qiu-Ning; Zhang, Dai-Zhen; Dai, Li-Shang
Abstract: To learn more about red swamp crayfish related genes in response to bacterial infections, we investigated immune-related genes induced by lipopolysaccharide (LPS) in the hepatopancreas using high-throughput sequencing method. In present the study, a total of 55, 107 unigenes were identified, with an average length of 678 bp. A total of 2215 differentially expressed genes (DEGs) were found, including 669 up-regulated genes and 1546 down-regulated genes. The result of Gene ontology (GO) analysis revealed that 3017 DEGs were enriched in 19 biological process subcategories, 17 cellular component subcategories and 15 molecular function subcategories. The top 20 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways showed that "ribosome" was the most abundant group, which had 34 DEGs. KEGG enrichment analysis identified several immune response pathways. Real-time quantitative reverse transcription-PCR (qRT-PCR) results exhibited that several immune responsive genes were greatly up-regulated following LPS stimulation as observed in the results of high-throughput sequencing. Overall, this study provides new insight into the immune defense mechanisms of P. clarkii against LPS infection. Highlights: The LPS-challenged Procambarus clarkii hepatopancreas transcriptomes was determined. Of 55107 unigenes identified, 2215 were differentially expressed after LPS challenge. Among the identified DEGs, 669 and 1546 were up- and down-regulated, respectively. The qRT-PCR results of the transcriptome validation candidate gene are consistent with those obtained by the transcriptome.